Substituted (сycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic(sulfonic) acids: synthesis, antimicrobial and growth-regulating activity - O. V. Kholodniak; V. V. Stavytskyi; S. I. Kovalenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Acylisothiocyanates are a promising class of organic compounds that are present in the plant world and can be used in the synthesis of disubstituted thioureas and various heterocycles. These derivatives are characterized by growth-regulating, antibacterial, fungicidal, cytotoxicity, and other activities. Modification of acylisothiocyanates by fragments of substituted aminoarylcarboxylic (sulfo) acids is promising, as some of them (anthranilic, p-aminobenzoic acids) are precursors for the auxins and other natural compounds synthesis. Their combined activity is also an important aspect. Namely the simultaneous manifestation of both fungicidal and restrictive activity. Based on this, the synthesis of new substituted (cycloalkylcarbonylthioureido)aryl-(benzyl-)carboxylic (sulfonic) acids is relevant as promising regulators of plant growth with antibacterial activity.